The Bradford community stroke trial: results at six months. Issue 6834 (25th April 1992) - Young, J. B.; Forster, A.
Abstract : OBJECTIVE–Comparison of day hospital attendance and home physiotherapy for stroke patients leaving hospital to determine which service produces greater functional and social improvement for the patient, reduces emotional stress for the care giver, and lessens the need for community support. DESIGN–Stratified, randomised trial of stroke patients attending day hospital two days a week or receiving home treatment from a community physiotherapist. The six month assessment results are reported in this paper. SUBJECTS–Patients over 60 years old resident within the Bradford metropolitan district discharged home after a new stroke with residual disability. SETTING–Four day hospitals in two health authorities and domiciliary work undertaken by experienced community physiotherapists. MAIN OUTCOME MEASURES–Barthel index, functional ambulatory categories, Motor Club assessment, Frenchay activities index, and Nottingham health profile were used. Carers' stress was indicated by the general health questionnaire. Treatment given and community care provided were recorded. RESULTS–Of 124 patients recruited, 108 were available for reassessment at six months. Both treatment groups had significantly improved in functional abilities between discharge and six months. The improvements were significantly greater for patients treated at home (Mann-Whitney test; Barthel index, median difference 2 (95% confidence interval 0 to 3) p = 0.01; Motor Club assessment, median difference 2 (1 to 5), p = 0.01). The home treated patients received less treatment (median difference 16 (11 to 21) treatments, p less than 0.001). More than a third of patients in both groups showed depressed mood, and a quarter of care givers were emotionally distressed. CONCLUSIONS–Home physiotherapy seems to be slightly more effective and more resource efficient than day hospital attendance and should be the preferred rehabilitation method for aftercare of stroke patients. New strategies are needed to address psychosocial function for both patients and care givers.